In House Training Peningkatan Kemampuan Guru dalam Menerapkan Authentic Assesment dalam Proses Belajar Mengajar - Wahyani, Widhy; Sukarsono, Agustin; Syaichu, Achmad (Proceedings of Annual Conference on Community Engagement, 2018)
One form of evaluation of the implementation of in house training activities carried out is a reflection of the activities carried out by participants. In general, participants stated that this training activity provided new insights to teachers, especially in authentic assessments, especially performance appraisal and attitude assessment. This is because there are still many teachers who assess the performance of students not using the assessment rubric. Another thing raised by participants was the attitude assessment instrument. So far the teacher has assessed students' attitudes without clear guidelines. With this training, the teacher especially the training participants get a new experience and lessons in assessing student attitudes. Another reflection expressed by the participants was that it was not easy to compile an assessment rubric because the rubric had to be measured and they suggested that with this training it opened up new insights for the teachers in conducting assessments with rubrics. This shows that this in-house training activity has had a positive impact on the participants. There is a desire to change the mindset and try to do activities that are different from previous activities, especially in assessing learning in class.